PROVERBIAL PHRASEOLOGICAL UNITS AS A REFLECTION OF ENGLISH NATIONAL CULTURE - Sh. K. Kayumova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article discusses phraseological units and features of their use as a way to reflect the features of the national culture of the English people. Phraseological units are a mirror of the nation. They fully reveal the national specificity of the language, its identity. No matter what other means of language, they absorb history best of all, express the mentality peculiar to the people, the way of thinking, the peculiarity of the view; they show everyday life, spirit and character, mores and customs, beliefs and superstitions.